Inkâr al-Sunnah pada Aspek Kodifikasi Hadis - Mz, Zainuddin (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2013)
One aspect that makes a bunch of people does not believe in the existence and role of sunnah is the delay of codification itself. Peoples also considered that hadith’s codified in various references are not what are worth ascribed to the Prophet, but rather a form of the companions comprehension of the Prophet’s directives and statements. That is why, there are different editorial ranges between one companion to another, even the mutawâtir lafzî was not separated from this editorial differences. This paper high lights how was the process of hadith codification, so that we can find a common points which are closely related to the authenticity and validity of a hadith. Studying on such topic (the process of hadith codification and classification), shows how professional the hadith scholars in memorizing and maintaining Sunnah of the Prophet, to bring the science of isnâd (‘ilm al-isnâd) which is never possessed by any other religion. This is the climax of the way clergy maintaining the authenticity of the Prophet sayings. That is, whenever one states todays about a hadith, definitely, its authenticity and validity would be detected through the scienc.